Nine years review of emergency peripartum hysterectomy at tertiary care university teaching hospital (Journal of Patan Academy of Health Sciences, 2016)
Introductions: This study documented the frequency, indications, and outcome of emergency obstetric hysterectomies in a tertiary care hospital in Nepal.Methods: This was a nine years retrospective study of peripartum hysterectomy at Patan Hospital, Patan Academy of Health Sciences, Nepal, during 2006 to 2014. Patients’ charts were retrieved from the medical record section for review. Study variables included previous obstetric history, details of the index pregnancy, indications for peripartum hysterectomy, outcome of the hysterectomy and infant morbidity.Results: There were total of 73,130 deliveries. Emergency peripartum hysterectomies were performed in 28 (0.04%), of which 23 (82%) after cesarean and 5 (18%) after vaginal delivery. The primary indication for hysterectomy was uterine atony with postpartum hemorrhage (PPH), and placental causes with PPH and uterine rupture. Twelve (43%) patients had postoperative complications. There was one maternal and two neonatal mortalities, and one stillbirth.Conclusion: The rate of emergency peripartum hysterectomy in our institute is low at 0.04%, indications were primarily due to uterine atony with postpartum hemorrhage.Journal of Patan Academy of Health Sciences, Vol. 3, No. 1, 2016. page:23-26